2015
DOI: 10.1097/jto.0000000000000484
|View full text |Cite
|
Sign up to set email alerts
|

Central versus Peripheral Tumor Location: Influence on Survival, Local Control, and Toxicity Following Stereotactic Body Radiotherapy for Primary Non–Small-Cell Lung Cancer

Abstract: Central tumor location did not predict for inferior OS, LC, or toxicity following SBRT when a lower mean BED was utilized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 17 publications
3
47
0
Order By: Relevance
“…One phase 3 study comparing SBRT and surgery (only the SBRT data was used) [12], 10 phase 2 [20-31], 1 phase 1 [32], and 56 retrospective [33-51,53-89] photon SBRT studies were included in the survival outcome comparison analysis. Among them, treatment-related toxicities were reported in all the prospective studies [12,20-32], and 40 retrospective studies [34,37,39-40,42,44-47,49,52-61,65,67-73,76-78, 80-82,84-89]. These studies were included in the treatment-related toxicity comparison analysis.…”
Section: Resultsmentioning
confidence: 99%
“…One phase 3 study comparing SBRT and surgery (only the SBRT data was used) [12], 10 phase 2 [20-31], 1 phase 1 [32], and 56 retrospective [33-51,53-89] photon SBRT studies were included in the survival outcome comparison analysis. Among them, treatment-related toxicities were reported in all the prospective studies [12,20-32], and 40 retrospective studies [34,37,39-40,42,44-47,49,52-61,65,67-73,76-78, 80-82,84-89]. These studies were included in the treatment-related toxicity comparison analysis.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hands, there are some different reports about SBRT. One has been reported that tumor location was not associated with worse prognosis for patients treated with SBRT, 40 and the other has been reported central tumors increased risk of high-grade toxicity or death. 41 Lebioda et al 42 reported that the risk of mediastinal nodal involvement in NSCLC patients with clinically negative N2 lymph nodes was significantly high for central tumor location.…”
Section: Discussionmentioning
confidence: 98%
“…Patients meeting all inclusion criteria underwent chart review for type of oncologic treatment, clinical outcome, and MAC treatment regimen. Additionally, chest imaging from initial lung cancer diagnosis was reviewed, when available, and tumors were classified as central if they were within 2 cm of the proximal bronchial tree or other mediastinal structures [14].…”
Section: Methodsmentioning
confidence: 99%